Skin microcirculatory responses: A potential marker for early diabetic neuropathy assessment using a low‐cost portable diffuse optical spectrometry device - Vasudevan, Vysakh; Unni, Sujatha Narayanan (Journal of biophotonics, 2024)
Diffuse optical measurement is an evolving optical modality providing a fast and portable solution for microcirculation assessment. Diffuse optics in static and dynamic modalities are combined here in a system to assess hemodynamics in skin tissues of control and diabetic subjects. The in‐house developed system consists of a laser source, fiber optic probe, a low‐cost avalanche photodiode, a finite element model (FEM) derived static optical property estimator, and a software correlator for continuous flow monitoring through microvasculature. The studies demonstrated that the system quantifies the changes in blood flow rate in the immediate skin subsurface. The system is calibrated with in vitro flow models and a proof‐of‐concept was demonstrated on a limited number of subjects in a clinical environment. The flow changes in response to vasoconstrictive and vasodilative stimuli were analyzed and used to classify different stages of diabetes, including diabetic neuropathy. The system is proposed and demonstrated for estimating skin perfusion at lower extremities subjects with varying stages of diabetes mellitus. The novel concept of employing diffuse correlation spectroscopy at short source to detector separation and utilization of a static parameter estimator from a pre‐defined look‐up table modelled from human skin tissue parameters using FEM provides a viable alternative to detect the onset of diabetic neuropathy via assessing microcirculation.